2023
DOI: 10.3389/fpsyg.2023.1229653
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Italian students’ self-ratings on the SSIS SEL brief scales

Valeria Cavioni,
Elisabetta Conte,
Ilaria Grazzani
et al.

Abstract: IntroductionDespite increasing interest in measuring social and emotional learning (SEL), there is a lack of European-validated tools for assessing the efficacy of SEL programs. The aim of this study was to validate an Italian version of the social skills improvement system (SSIS) SEL brief scales–student form.MethodsParticipants were 1,175 students (mean age: 11.02 years; SD: 2.42; range: 8–16 years; males: 46.8%) recruited at schools in Northern Italy.Statistical analyses and resultsInitial confirmatory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The major goal of development was to develop an efficient measure well-adapted for use in schools' multi-tiered support systems targeting students' SEL development. Initial evidence has supported the psychometric quality of scores from the SSIS SELb (Anthony et al, 2020a;2020b;Elliott et al, 2021) and subsequent evidence has corroborated this conclusion (e.g., Anthony et al, 2021;Cavioni et al, 2023a).…”
Section: The Ssis-sel Brief Scalesmentioning
confidence: 95%
“…The major goal of development was to develop an efficient measure well-adapted for use in schools' multi-tiered support systems targeting students' SEL development. Initial evidence has supported the psychometric quality of scores from the SSIS SELb (Anthony et al, 2020a;2020b;Elliott et al, 2021) and subsequent evidence has corroborated this conclusion (e.g., Anthony et al, 2021;Cavioni et al, 2023a).…”
Section: The Ssis-sel Brief Scalesmentioning
confidence: 95%
“…This involved examining studies that investigated the various factors influencing teachers' wellbeing considering both at risk-factors, including work-related stress, burnout, and emotional exhaustion, and protective factors, namely the core components of social and emotional learning (SEL) such as self-awareness, self-management, social awareness, relationship skills, and responsible decision-making (Mahoney et al, 2021 ; Ornaghi et al, 2023 ). The literature analysis also examined the importance of SEL for educators, its impact on teacher-student relationships, classroom climate, and students' wellbeing, as well as the potential consequences on the broader educational environment (Domitrovich et al, 2017 ; Cavioni et al, 2023a ; Conte et al, 2023 ).…”
Section: The “Online Wellbeing Course”mentioning
confidence: 99%
“…Numerous studies have shown that the teaching profession is among those with the highest levels of work-related stress since teachers are often exposed to a series of difficulties and challenging situations that can negatively affect their mental wellbeing (Chang, 2009;OECD, 2019). The workload, the management of students' social, emotional, and behavioral problems in the classroom, the responsibility for their physical and psychological health, the partnership between the school and the family as well as the low salary are listed as the most significant stressors which require considerable emotional effort (Cavioni and Grazzani, 2023;Cavioni et al, 2023b;Conte et al, 2024). Furthermore, the COVID-19 pandemic has profoundly impacted societies worldwide, with widespread disruption and unprecedented challenges in various domains, including education (Colomeischi et al, 2022;Martinsone et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These educators assume the role of catalysts in nurturing a school climate that fosters positivity and wellbeing amongst students (Ornaghi et al, 2022). This, in turn, sparks their engagement and promotes their academic accomplishments (Cavioni et al, 2023a). As a result, when teachers are allowed to make their well-being a priority, they initiate a domino effect that resonates across the entire educational environment, transcending the boundaries of their personal and professional development (Lester et al, 2020).…”
Section: Well-being and Work Engagementmentioning
confidence: 99%